Extended Arm - Stelarc, Stelarc (New Romance, 2015)
The inspiration for this exhibition was William Gibson’s SF work “Neuromancer” (1984), a seminal cyberpunk novel about modified bodies and virtual reality. When Gibsons book was translated into Korean, it was mistakenly translated as “New Romance”. The exhibition sought transdisciplinary and transnational art works to reflect the contemporary ‘new romance’ with machine aesthetics and new media. In the performance with his “Extended Arm”, an enhanced articulated human arm exoskeleton that is added to one side of the artist’s body, while his other arm is subject to involuntary movement via a preprogrammed muscle stimulation system. The “Extended Arm” performance simultaneously realizes a representation of science fiction’s futuristic hopes of augmentation and its fear of loss of control, while the “Extended Arm” installation demonstrates the cyborg aesthetic of altered bodies. The intense and complex performance has been presented only four times, with each performance unique in visual setting, sound and effects, and contextually differentiated.